2017
DOI: 10.9788/tp2017.4-15
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Memory Decline in the Elderly

Abstract: Objective: To analyze the memory performance of participants aged 60 years and older with and without depressive symptoms. Methods: 199 participants were assessed using the Beck Depression Inventory (BDI) with a cut-off point of 20 for depression. Of these, 22 met the criteria for depression group; the remaining participants were allocated to the non-depression group. The Rey Auditory-Verbal Learning Test (RAVLT) was used to assess verbal learning, fi gures I and II of the Visual Reproduction subtest of the We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Data also showed that our version of the T5P allows us to accurately discriminate the AD group from the MCI one with mild sensitivity but high specificity. The ability of the T5P to distinguish between AD, MCI and functional memory disorders appears crucial in the differential diagnosis of memory disturbances because the normal age-related reduction of memory performances can be exacerbated by different pathological conditions such as depression [27]. Thus, AD amnesic syndrome can be sometimes confused with functional memory dysfunction due to depression [28].…”
Section: Discussionmentioning
confidence: 99%
“…Data also showed that our version of the T5P allows us to accurately discriminate the AD group from the MCI one with mild sensitivity but high specificity. The ability of the T5P to distinguish between AD, MCI and functional memory disorders appears crucial in the differential diagnosis of memory disturbances because the normal age-related reduction of memory performances can be exacerbated by different pathological conditions such as depression [27]. Thus, AD amnesic syndrome can be sometimes confused with functional memory dysfunction due to depression [28].…”
Section: Discussionmentioning
confidence: 99%